Management by roaming and self-efficacy and their impact on the excellence of hotel service: An applied study - Abbas, Mohammed Fadhil; Abdullh, Mohammed Hasan (Journal of Economics and Administrative Sciences, 2021)
This research investigates the type and the significant relationship between roaming management and self-efficacy and its impact on excellence in providing hotel service. To achieve this, the applied approach was adopted through A questionnaire was designed and developed for the collected data. It has consisted of three parts. The firsts section included nine questions to measure the dimensions of management by roaming. The second section includes nine questions to measure the effectiveness of the two employees. The last section includes 12 questions to measure the excellence of the hotel service. The research sample included 43 employees’ responding to this survey to measure the two independent variables—also, 45 of the guests responding to this survey to measure the adopted variable. The final results indicated there is a significant direct correlation between management, roaming, and self-efficacy, which has an impact on the excellence of hotel service. The most important recommendations of this study were: achieving excellence in providing hotel service requires a work environment that supports senior management in the field of work. In addition to its ideal investment of workforce potentials and enabling them to provide the best performance, Through that, the research provides what qualifies them towards the excellence in their services to the customer